Economic Empowerment Through Productive Zakat: A Community-Based Approach - Humaidah, Lisma; Noor Hasvenda Abd Rahim (Journal of social Philantrophy and Halal Research, 2024)
Economic empowerment through productive zakat is an effort to free ourselves from the shackles of poverty with zakat funds provided to be developed and used to support sustainable businesses. This study aims to identify how the productive zakat economic empowerment model and the impact felt by poor orphan mothers before and after receiving BISA program assistance at LAZNAS Yatim Mandiri Surabaya. This study uses a descriptive qualitative research method to describe the problem. Data were collected using interview, observation, and documentation techniques. The results of the study indicate that the economic empowerment model through the distribution of productive zakat in the BISA program will reduce family economic problems through empowerment activities carried out, namely forming BISA groups, religious guidance, distribution of business capital and coaching training